2019
DOI: 10.1093/nsr/nwz160
|View full text |Cite
|
Sign up to set email alerts
|

De novoassembly of a Tibetan genome and identification of novel structural variants associated with high-altitude adaptation

Abstract: Structural variants (SVs) may play important roles in human adaptation to extreme environments such as high altitude but have been under-investigated. Here, combining long-read sequencing with multiple scaffolding techniques, we assembled a high-quality Tibetan genome (ZF1), with a contig N50 length of 24.57 mega-base pairs (Mb) and a scaffold N50 length of 58.80 Mb. The ZF1 assembly filled 80 remaining N-gaps (0.25 Mb in total length) in the reference human genome (GRCh38). Markedly, we detected 17 900 SVs, a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 42 publications
3
36
0
Order By: Relevance
“…These 35 scaffolds totalled 443,618,927 bp, meaning that ~98.5% of the genome was assigned to the chromosomes (Table 2). Because the orientations of the scaffolds were not experimentally determined and sizes of gaps between scaffolds are unknown, chromosome‐scale scaffolding techniques, Hi‐C sequencing (Burton et al., 2013; Dudchenko et al., 2017) or optical mapping (Jiao et al, 2017; Ouzhuluobu et al., 2020) would be desirable.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These 35 scaffolds totalled 443,618,927 bp, meaning that ~98.5% of the genome was assigned to the chromosomes (Table 2). Because the orientations of the scaffolds were not experimentally determined and sizes of gaps between scaffolds are unknown, chromosome‐scale scaffolding techniques, Hi‐C sequencing (Burton et al., 2013; Dudchenko et al., 2017) or optical mapping (Jiao et al, 2017; Ouzhuluobu et al., 2020) would be desirable.…”
Section: Resultsmentioning
confidence: 99%
“…These 35 scaffolds totalled 443,618,927 bp, meaning that ~98.5% of the genome was assigned to the chromosomes (Table 2). Because the orientations of the scaffolds were not experimentally determined and sizes of gaps between scaffolds are unknown, chromosome-scale scaffolding techniques, Hi-C sequencing (Burton et al, 2013;Dudchenko et al, 2017) or optical mapping (Jiao et al, 2017;Ouzhuluobu et al, 2020) (Figure 2). Interestingly, although the total length of LINE and its proportion of all repetitive sequences in the genome were similar between S. ricini and B. mori (Figure 2), the components of LINE families were different.…”
Section: Overview Of Samia Ricini Genome Assemblymentioning
confidence: 99%
“…1f), the majority of which were low-frequency (allele frequency<0.1, ~58%) and singleton SVs (~29.9%) (Supplementary Table 4). We also compared our Tibetan SV set with the ZF1 SV call set, which was recently collected from a high-quality de novo assembled Tibetan genome based on the SMRT platform 16 . We found that only 15,890 SVs (~17%) in our Tibetan SV reference panel overlapped with the ZF1 SV call set (17,714 SVs) (Supplementary Table 5).…”
Section: Comparison With Existing Sv Call Setsmentioning
confidence: 99%
“…Medical genetics has taken a leap forward in personalized medicine with the information of whole genome sequence for inheritable conditions, birth defects and chromosomal disorders 6 . Personalized genome assembly has shed light on the effects that non-genetic, disease-linked etiologies like methylation of CpG base pair islands have on gene availability for transcription 7,8 .…”
Section: Introductionmentioning
confidence: 99%
“…Medical genetics has taken a leap forward in personalized medicine with the information of whole genome sequence for inheritable conditions, birth defects and chromosomal disorders 6 .…”
Section: Introductionmentioning
confidence: 99%